Tyre and vehicle dynamics - Pacejka, H. B. (Oxford : Butterworth-Heinemann, 2006)
In this new paperback edition of Tyre and Vehicle Dynamics, theory is supported by practical and experimental evidence. Pacejka provides both basic and advanced explanations of the pneumatic tyre and its impact on vehicle dynamic performance. The book shows the way in which tyre models are incorporated in vehicle models and how important tyre influence is on overall vehicle behaviour. Those working in any industry involving equipment with tyres will continue to find this book both extremely relevant and useful. * Written by a world expert in tyre dynamics * Covers both basic and advanced tyre modelling and simulation, including case studies of application examples and chapter exercises * Indispensable for any engineer working in vehicle system dynamics and for any industry involving equipment with tyres.
Tyre characteristics and vehicle handling and stability; Basic tyre modelling considerations; Theory of steady-state slip force and moment generation; Semi-empirical steady-state tyre models; Non-steady-state out-of-plane string-based tyre model; Theory of the wheel-shimmy phenomenon; Single contact point transient tyre models; Applications of transient tyre models; Short wavelength intermediate frequency tyre model; Dynamic Tyre Model Performance; Motorcycle dynamics; Steady state and dynamic tyre testing; References; Appendix; List of symbols; Index.
Includes bibliographical references (p. [595]-605) and index.
Keywords: Tires -- Design; Tires -- Traction; Motor vehicles -- Tires; Motor vehicles -- Dynamics; Electronic books